Fabrication of reinforced hydrophobic coatings for the protection of silk fabric. Issue 18 (September 2019) - Zhao, Suhua; He, Ru; Zhang, Xin; Zeng, Weichen; Zhang, Tianyi; Yu, Weidong; Liu, Hongling
The design of water-resistance and breathable materials applied to the protection of a historical silk textile has raised considerable interest for their highly practical potential. Thus, simple and functional composite coatings have been investigated and applied on Bombyx mori silk fabrics by spraying silk fibroin and a water soluble siloxane emulsion enriched with silica nanoparticles (12 nm). The layer of spraying silk fibroin on the surface of the silk fabric resulted in mesoscopic molecular network reconstruction by hydrogen bonds and crosslinking of ethylene glycol diglycidyl ether to improve the physical property of the silk fabric. By systematically investigating silica composite treatment, it was found that the sample treated with silica composite coatings possessed a good hydrophobic property, in which the static contact angles increased from 43.27° to 145.77° for uncoated and coated samples, respectively. As determined by Fourier transform-infrared spectroscopy analyses, hydrophobic components such as Si-O-Si, Si-O were successfully attached to the silk fabric. The scanning electron microscopy images and the energy-dispersive X-ray spectroscopy map point distribution images showed that the coating of the silica composite forms a uniform nano-scale structure, which improved the waterproof and breathable performance. Compared with uncoated fabric, the silica composite treatment was endowed with enhanced air permeability of 446.47 mm/s. After the abrasion and washing cycles, high durability of the coated fabric was demonstrated. Excellent hydrophobic capability could help silk fabric avoid the destruction of any harmful pollutant, such as light, bacteria, sewage and so on. Furthermore, the proposed relationship between the adhesive structure and the waterproof/breathable property is applicable in the design of functional silk textiles with different levels for protective performance.